BIOEQUIVALENCE STUDY OF A 400 MG INTRAVAGINAL PROGESTERONE PESSARY USING TANDEM MASS SPECTROMETRY IN FEMALE SUBJECTS - ABU-AWWAD, AHMAD; ARAFAT, BASIL; ARAFATE, TAWFIQ (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to evaluate the bioequivalence of 400 mg single pessary dose for intravaginal progesterone test product in pilot study followed by a full study compared to the reference product, Cyclogest®. The test product represents a newly developed intravaginal progesterone formulation designed to achieve bioequivalent Pharmacokinetic (PK) parameters to Cyclogest®. Methods: The test product was initially studied in six healthy adult females following a randomized, two-way crossover design under fasted state. The results from the pilot study were further confirmed in full study of 38 subjects. Progesterone with progesterone-D9 as the internal standard, was extracted and quantified from human plasma samples using LC-MS/MS after a direct precipitation extraction procedure. The developed method was validated over a dynamic range of 0.3–25 ng/ml in accordance with US-FDA, EMEA, and ICH guidelines. Results: All validation results were within the acceptance criteria. The geometric mean values for the main PK parameters from the pilot bioequivalence study for the test product were Cmax= 13.094 ng/ml and AUC0-t= 168.786 h. ng/ml, compared to the results of reference product (Cmax=11.920 ng/ml and AUC0-t = 154.339 h. ng/ml), which were in agreement with the corresponding results obtained from the full study for test product (Cmax= 15.175 ng/ml and AUC0-t = 202.669 h. ng/ml) compared to the results of reference product (Cmax= 13.359 ng/ml and AUC0-t = 206.423 h. ng/ml). Conclusion: The investigated test progesterone product was bioequivalent to the reference product.